2009
DOI: 10.1007/s10508-009-9527-1
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Probability of Conception Is Associated with their Preference for Flirtatious but not Masculine Facial Movement

Abstract: Women's preferences for facial structure vary over the menstrual cycle. Little is known, however, as to how preferences for behavior may be influenced by hormonal factors. Here, we demonstrate that social properties of facial motion influence attractiveness judgments in the absence of other cues, and that women's preferences for these displays vary over the menstrual cycle, as has been demonstrated for structural traits of men's faces in static stimuli. We produced shape-standardized facial models that were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…The phase of the menstrual cycle in which women made their judgments is known to affect attractiveness judgments in static (Penton‐Voak et al. 1999, Penton‐Voak and Perrett 2000) and moving (Morrison et al. 2009) faces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase of the menstrual cycle in which women made their judgments is known to affect attractiveness judgments in static (Penton‐Voak et al. 1999, Penton‐Voak and Perrett 2000) and moving (Morrison et al. 2009) faces.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, motion‐capture techniques have shown that body movement can indicate body symmetry (Brown et al. 2005), and facial movement can indicate emotional expression (Bassili 1978, 1979; Rubenstein 2005) and flirtatiousness (Morrison et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Motion-capture studies of human gait have shown that women prefer masculine movement, especially when they are in the fertile phase of their menstrual cycles and when they are more open to short-term mating (Provost, Troje & Quinsey, 2008). These findings parallel work on facial motion, which suggests that sex-typical movement is attractive in female faces (Morrison, Gralewski, Campbell, & Penton-Voak, 2007), and that women's preferences shift across the menstrual cycle (Morrison, Clark, Gralewski, Campbell, & Penton-Voak, 2009). Women's gait itself changes across the menstrual cycle, but, surprisingly, men prefer the gait of women in the luteal, non-fertile phase (Provost, Quinsey, & Troje, 2008).…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, previous research has also reported changes in women’s flirting behavior and behavioral engagement with men displaying purported markers of genetic fitness (Cantú et al, 2014; Flowe, Swords, & Rockey, 2012). Women also seem to show preferences for flirtatious facial movement in the fertile phase of the ovulatory cycle (Morrison, Clark, Gralewski, Campbell, & Penton-Voak, 2010). Yet there are a lack of well-powered replications investigating preference shifts for men’s behavior (Jones, Hahn, & DeBruine, 2019).…”
Section: Overview Of the Current Study And Hypothesesmentioning
confidence: 99%